THE EFFECTS OF ANNEALING ON MICROSTRUCTURAL CHANGES FOR ALUMINIUM NITRIDE EPITAXIAL GROWN ON SAPPHIRE BY TRANSMISSION ELECTRON MICROSCOPY /lcJESBAINS KAUR - Jesbains Kaur, 1983-, author; Kuwano, Noriyuki, Dr., supervisor; Khairur Rijal Jamaludin, Assoc.Prof.Dr., supervisor; Institut Teknologi Antarabangsa Malaysia - Jepun (Kuala Lumpur : Universiti Teknologi Malaysia, 2017)
Thesis (PhD)